Different types of suppression-burst patterns in patients with epilepsy of infancy with migrating focal seizures (EIMFS). (February 2019) - Yoshitomi, Shinsaku; Takahashi, Yukitoshi; Imai, Katsumi; Koshimizu, Eriko; Miyatake, Satoko; Nakashima, Mitsuko; Saitsu, Hirotomo; Matsumoto, Naomichi; Kato, Mitsuhiro; Fujita, Takako; Ishii, Atsushi; Hirose, Shinichi; et al.
Abstract: Purpose: In rare cases, patients with epilepsy of infancy withmigrating focal seizures (EIMFS) exhibit suppression-burst (SB) patterns on electroencephalography (EEG), similar to the findings observed in patients with Ohtahara syndrome and early myoclonic encephalopathy. In this report, we discuss six cases of EIMFS in which patients exhibited two types of SB patterns. Methods: We evaluated six patients with EIMFS who had been admitted to the NHO Shizuoka Institute of Epilepsy and Neurological Disorders between 2011 and 2018. We retrospectively examined clinical characteristics and EEG findings for each patient. In all patients, the first EEG was performed within 1 month after seizure onset. Afterwards, EEG examinations were performed at irregular intervals (ranging from 1 to 5 months). Results: Age at seizure onset ranged from 2 days to 3 months. SB was first detected within 1 month of age in two patients, and within the range of 3–14 months in the remaining four patients. Among the latter four patients, SB patterns persisted at the final EEG recording in three patients (34–54 months). In all patients, SB patterns were observed during sleep only. Interhemispheric asynchrony in SB was observed in the two patients who exhibited SB within 1 month of age, while synchronous SB patterns were observed in the remaining four patients. Conclusions: Our findings indicate that EIMFS may be associated with two types of SB patterns (early-onset and late-onset), which can be distinguished based on the stage of emergence and level of synchrony.